Assessment of Dietary Patterns in Thyroid Patients in Zawia City, Libya - Amina Elzawi,; Nadia Beshna,; Ghufran Alahrash,; Shahd Alafia,; Aya Alearf, (AlQalam Journal of Medical and Applied Sciences, 2024)
Hormonal abnormalities, especially those related to follicle-stimulating hormone (FSH). This study seeks to examine the relationships of BMI, dietary patterns, seafood intake, FSH levels, and genetic variables in patients with thyroid conditions. This cross-sectional study encompassed 94 patients with thyroid conditions. BMI was categorized into four classifications (<17, 17–19, 20–25, >25), and dietary patterns were divided into conventional, balanced, specific diets, and others. Seafood consumption was classified as daily, weekly, seldom, infrequently, or never. FSH levels were categorized into five ranges. Statistical analysis was conducted to evaluate the correlations among these characteristics. A significant correlation was seen between BMI and FSH levels (p = 0.000041), with people exhibiting a BMI <17 demonstrating elevated FSH levels (>15 in 10 participants). Individuals with a BMI exceeding 25 demonstrated reduced FSH levels (ranging from 1 to less than 5 in 18 subjects). Seafood consumption significantly influenced FSH levels (p = 0.002334), with weekly consumers exhibiting a wide range of FSH values, whereas infrequent or non-consumers demonstrated elevated FSH levels (>15 in 5 subjects). Concerning dietary patterns, 60.63% adhered to a conventional diet, whereas 67% of patients have a familial history of thyroid disorders. Furthermore, 48.2% of subjects had second-degree obesity. This study highlights the intricate relationship among BMI, dietary habits, seafood intake, and hormonal regulation in patients with thyroid conditions. These factors, in conjunction with genetic predispositions, must be taken into account in the management of thyroid problems to enhance patient outcomes. الغدة الدرقية تتأثر بعوامل مختلفة، بما في ذلك مؤشر كتلة الجسم (BMI)، العوامل الوراثية، العادات الغذائية، والاختلالات الهرمونية، خاصة تلك المتعلقة بهرمون التحفيز الجريبي (FSH). تهدف هذه الدراسة إلى فحص العلاقة بين مؤشر كتلة الجسم، الأنماط الغذائية، استهلاك المأكولات البحرية، مستويات FSH، والعوامل الوراثية لدى المرضى الذين يعانون من اضطرابات الغدة الدرقية. شملت هذه الدراسة المقطعية 94 مريضًا يعانون من اضطرابات الغدة الدرقية. تم تصنيف مؤشر كتلة الجسم إلى أربعة تصنيفات (<17، 17–19، 20–25، >25)، كما تم تقسيم الأنماط الغذائية إلى نمط تقليدي، نمط متوازن، حميات خاصة، وأنماط أخرى. تم تصنيف استهلاك المأكولات البحرية إلى يومي، أسبوعي، نادر، بشكل غير متكرر، أو عدم الاستهلاك نهائيًا. تم تقسيم مستويات FSH إلى خمسة نطاقات: <1، من 1 إلى <5، من 5 إلى <10، من 10 إلى <15، وأكثر من 15. تم جمع البيانات حول الوراثة، وتم إجراء تحليل إحصائي لتقييم العلاقات بين هذه الخصائص. أظهرت النتائج وجود علاقة معنوية بين مؤشر كتلة الجسم ومستويات FSH (p = 0.000041)، حيث أظهر الأشخاص الذين لديهم مؤشر كتلة جسم أقل من 17 مستويات FSH مرتفعة (>15 في 10 مشاركين). أما الأفراد الذين تجاوز مؤشر كتلة الجسم لديهم 25 فقد أظهروا مستويات FSH منخفضة (تراوحت بين 1 وأقل من 5 في 18 شخصًا). كان لاستهلاك المأكولات البحرية تأثير كبير على مستويات FSH (p = 0.002334)، حيث أظهر المستهلكون الأسبوعيون نطاقًا واسعًا من قيم FSH، بينما أظهر غير المستهلكين أو المستهلكين بشكل غير متكرر مستويات FSH مرتفعة (>15 في 5 أشخاص). فيما يتعلق بالأنماط الغذائية، اتبع 60.63% نظامًا غذائيًا تقليديًا، في حين أن 67% من المرضى لديهم تاريخ عائلي لاضطرابات الغدة الدرقية. علاوة على ذلك، كان 48.2% من المشاركين يعانون من السمنة من الدرجة الثانية. تسلط هذه الدراسة الضوء على العلاقة المعقدة بين مؤشر كتلة الجسم، العادات الغذائية، استهلاك المأكولات البحرية، وتنظيم الهرمونات لدى المرضى الذين يعانون من اضطرابات الغدة الدرقية. يجب أخذ هذه العوامل، جنبًا إلى جنب مع الاستعدادات الوراثية، في الاعتبار عند إدارة مشاكل الغدة الدرقية لتحسين النتائج العلاجية للمرضى